Biết \(F\left( x \right) = - \dfrac{1}{{{x^2}}}\) là một nguyên hàm của hàm số \(y = \dfrac{{f\left( x \right)}}{x}.\) Tính \(\int {f'\left( x \right)\ln xdx.} \)

Câu hỏi :

Biết \(F\left( x \right) =  - \dfrac{1}{{{x^2}}}\) là một nguyên hàm của hàm số \(y = \dfrac{{f\left( x \right)}}{x}.\) Tính \(\int {f'\left( x \right)\ln xdx.} \) 

A. \(\int {f'\left( x \right)\ln xdx}  =  - \dfrac{{2\ln x}}{{{x^2}}} + \dfrac{1}{{{x^2}}} + C\) 

B. \(\int {f'\left( x \right)\ln xdx}  = \dfrac{{2\ln x}}{{{x^2}}} + \dfrac{1}{{{x^2}}} + C\) 

C. \(\int {f'\left( x \right)\ln xdx}  = \dfrac{{2\ln x}}{{{x^2}}} - \dfrac{1}{{{x^2}}} + C\) 

D. \(\int {f'\left( x \right)\ln xdx}  =  - \dfrac{{2\ln x}}{{{x^2}}} - \dfrac{1}{{{x^2}}} + C\) 

* Đáp án

B

* Hướng dẫn giải

Đặt \(\left\{ \begin{array}{l}\ln x = u\\f'\left( x \right)dx = dv\end{array} \right. \Leftrightarrow \left\{ \begin{array}{l}\dfrac{1}{x}dx = du\\v = f\left( x \right)\end{array} \right.\)

Ta có \(\int {f'\left( x \right)\ln xdx}  = \ln x.f\left( x \right) - \int {\dfrac{1}{x}f\left( x \right)dx}  = \ln x.f\left( x \right) + \dfrac{1}{{{x^2}}} + C\)

(vì theo giả thiết \(\int {\dfrac{{f\left( x \right)}}{x}dx}  =  - \dfrac{1}{{{x^2}}} + C\))

Lại có \({\left( {F\left( x \right)} \right)^\prime } = \dfrac{{f\left( x \right)}}{x} \Leftrightarrow \dfrac{{f\left( x \right)}}{x} = {\left( { - \dfrac{1}{{{x^2}}}} \right)^\prime } \Leftrightarrow \dfrac{{f\left( x \right)}}{x} = \dfrac{2}{{{x^3}}} \Rightarrow f\left( x \right) = \dfrac{2}{{{x^2}}}\)

Suy ra \(\int {f'\left( x \right)\ln xdx}  = \ln x.f\left( x \right) + \dfrac{1}{{{x^2}}} + C = \dfrac{{2\ln x}}{{{x^2}}} + \dfrac{1}{{{x^2}}} + C.\)

Chọn B

Copyright © 2021 HOCTAP247